Tax Moral on the Compliance of the Individual Taxpayers in Qardho District, Somalia (American Journal of Society and Law, 2023)
This study assessed the role of knowledge on the compliance of individual taxpayers, as well as impact of tax moral on the compliance of individual taxpayers and explored strategic solutions to cope tax moral on the compliance of individual taxpayers. The study applied a quantitative research method the data was collected sample size of 80 respondents including business owners, employees, local government staff, and unemployed through questionnaires were self-administrated with used likert scale. The procedure selected in this study will be simple random sampling method. The data were analyzed using descriptive statistics by SPSS to determine the demographic information relevant to the study were asked the respondents their ages as the data indicates, a huge number of the participants 24 (29.6%) fall in the 20 and 30 ages range. This means more than 78% of the survey respondents were youth, and it is quite understandable because, according to UN reports, more than 75% of the Somali population is less than 30 years old. The majority respondents Out of the 80 respondents, 47, or 58.0%, were males compared to 32 females, or 39.5%. This indicates a male domination of the study; there are cultural issues in the country that allow male to outnumber females in the job opportunities. The study has pointed up the role of knowledge on the compliance of individual taxpayers were not met a good moral tax administration, that may cause the taxpayers to be lack of coherent social contract and then that encouraged on refuse paying taxes, at the moment the poor tax moral system it that may lead non-compliance, and also emphasized tax administration teams faced more challenges as effected evasion of taxes, corruption, lower of income level, administration sanctions and lack of accountability. The study suggests that the local government should prioritize creating written laws of taxes, also must be done enforcement together efforts of the effectiveness of tax system in both the government and taxpayers, Furthermore, government should interest structuring tax laws to minimize non-compliance is essential.